Aberrant Right Subclavian Artery-Esophageal Fistula in 20-Year-Old with VATER Association - Kudose, Satoru; Pineda, Jose; Saito, Jacqueline M.; Dehner, Louis P. (Journal of Pediatric Intensive Care, 2017)
Aberrant right subclavian artery (ARSA), the most common aortic arch abnormality, occurs in approximately 0.5 to 1.8% of the general population, with prevalence of up to 25% in those with esophageal atresia. Although ARSA is often asymptomatic, a fistulous tract into esophagus may develop with prolonged nasogastric tube placement or endotracheal intubation and lead to potentially fatal hematemesis. We present a first case of ARSA-esophageal fistula in a 20-year-old woman with VATER association in the absence of an esophageal anomaly and review 28 cases of ARSA-esophageal fistula reported in the literature to date. Requiring nasogastric and endotracheal tube placement for approximately 4 months, the patient had a prolonged hospital course and died after sudden hematemesis. An autopsy demonstrated an ARSA-esophageal fistula and no other source of upper gastrointestinal bleeding. In patients with esophageal atresia requiring prolonged placement of an endotracheal or nasogastric tube, a screening imaging study and corrective surgery may be indicated. Although the mortality rate is still high, timely recognition and repair of ARSA-esophageal fistula appear to be improving. Given the potentially prolonged latency for its development with occasional presence of heralding symptoms, increased awareness may facilitate surgical intervention to prevent a catastrophic exsanguination.
Keywords: aberrant right subclavian artery; esophageal fistula; VATER association